Lumbar arteries with uncommon patterns of origin - (:unkn) unknown (My University, 2000)
Multiple variations of the origin the lumbar arteries were observed during the dissection of the abdominal aorta in a 44 year old male cadaver. A total of four pairs of the lumbar arteries were present. The 1st and 2nd pairs emerged from the posterior aspect of the abdominal aorta separately, while the 3rd pair emerged via a common trunk. The 4th right lumbar artery arose from the lateral aspect of the aorta 1.3 mm above aortic bifurcation while the left one arose 0.3 mm above bifurcation via a long common trunk with the median sacral artery. The variant origin and/or course of lumbar arteries could increase the risk of vascular injury, during the surgical and diagnostic procedures within the retroperitoneal region. Significance of lumbar arteries and their variations will be discussed from both clinical and embriological standpoint.
Keywords: Common trunk; Lumbar artery; Variation